EFFECTS OF ORAL ALFACALCIDOL ON MATURATION OF DENDRITIC CELLS IN GRAVES' DISEASE PATIENTS: A DOUBLE-BLINDED RANDOMIZED CLINICAL TRIAL - Purnamasari, Dyah; Djauzi, Samsuridjal; Setiati, Siti; Harahap, Alida; Gde Pemayun, Tjokorda; Prihartono, Joedo; Soewondo, Pradana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Maturity level of dendritic cells (DC) plays a pivotal role in initiating and regulating autoimmunity. In graves' disease (GD), DCs have more active immune responses than those in healthy subjects. Our previous study demonstrated immunoregulatory effects of in vitro 1,25-D3 on maturation of DC in GD patients. This study aims to evaluate the effect of oral 1α-D3 on DC maturation in GD patients. Methods: Twenty five GD patients with thyrotoxicosis were divided into two groups: 12 GD patients receiving oral 1α-D3 and 13 GD patients receiving placebo, in addition to treatment of propylthiouracil. Comparison of DC maturation were performed before and after the oral 1α-D3. DC maturation was assessed based on the expression of DC markers (HLA-DR, CD80, CD40, CD83, CD14 and CD206) and the ratio of cytokines interleukin-12/IL-10. Results: After 8 weeks, 8 out of 12 GD patients in treatment group and 6 out of 13 GD patients in placebo group still had high fT4 level. The expression of CD80 decreased (p=0.48) and CD206 increased (p=0.47) insignificantly among treatment group. The IL-12/IL-10 ratio decreased along with the improvement of fT4 level in both groups. No difference of the IL-12/IL10 ratio between treatment and placebo group. Conclusion: The effects of oral 1α-D3 on DC maturation of GD patients have not been clearly demonstrated in this study yet.